Congenital solitary intrahepatic biliary cyst in infant: A rare case report - Anil Kumar Yadav; Jianghua Zhan; Shujian Zhang; Nita Yadav (Elsevier, 2018)
Solitary liver cysts (SLCs) are usually asymptomatic, uncommon and nonparasitic cysts of congenital origin, most frequently discovered during imaging studies. It may develop in the form of simple cyst and biliary cyst. The majority of the cysts that are discovered incidentally remain small. The etiology of SLC is unknown. Perioperative cholangiography is helpful to confirm the connection between cyst and biliary tree. In several clinical situations, including resection of malignant or benign biliary lesions, reconstruction of the biliary system using the Roux-en-Y jejunum limb should be performed as the standard procedure.